(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Joint scaling test x2 and non-allelic interaction scaling test (A, B, and C) and a six-parameter model was used to assess the effectiveness of the genetic model and calculates the genetic elements for days to heading, flag leaf area, (number of spikes / plant, number of grains/spike , 1000 - grain weight and grain yield/ plant (g) using six populations (P1, P2, F1, F2, BC1 and BC2) and triple test crosses analysis of two wheat crosses; 1. Gemmeiza11 X Misr1 and 2. Gemmeiza 12 X Misr2. A randomized complete block design with three replications was used. The obtained results indicated the importance of additive genetic variance (D) in the genetic control of days to heading and flag leaf area for Gimmeiza 12 X Misr2 in tow methods analysis and number of spikes / plant in two crosses in tow method analysis. Heritability in narrow sense was more than 0.50. While the dominant type controlling for the remaining traits in two crosses was determined to be the dominance genetic variance (H), the value of (H/D)05 was more than one for these characters and heritability in narrow sense was less than 0.50. Joint scaling test (X2) and non-allelic interaction (A, B, and C) demonstrated that a basic genetic model was sufficient to explain the inheritance of number of spikes/plant for Gemmeiza 12 X Misr1, epistasis played a great role of controlling remaining characters in two crosses. Additive (d) and additive X dominance (j) were significant for days to heading and number of grains /spike (1st and 2nd crosses), 1000 grain weight and grain yield / plant for 2nd cross. The digenic interaction type dominance X dominance (l) controlling days to heading (1st and 2nd crosses), Number of spikes per plant (1st cross), number of grains per spike, weight in 1000 grains, and yield in grains per plant (2nd cross). The main limiting variables for selecting the best breeding technique are thought to be an understanding of the type of gene action controlling mechanism of the yield and yield components paired with the reproduction system. These information are of great interest for plant breeder to release high yielding wheat cultivars as well as early mature ones.